PENGARUH PENDIDIKAN, TINGKAT UPAH DAN PENGANGGURAN TERHADAP PERSENTASE PENDUDUK MISKIN DI KABUPATEN/KOTA PROVINSI BALI - Dian Purnama Yanti Cok Istri; Marhaeni A A I N (PIRAMIDA, 2015)
One of the objectives of national development is to improve the performance of the economy in order to createjobs and organize a decent life for all the people who in turn will realize the welfare of the population. One of themain indicators of the success of national development is the rate of decrease in the number of poor people. Thepurpose of this study was to determine: 1) direct influence between education, wages, and unemployment to thepercentage of the poor; 2) the influence of education and the level of wages indirectly to the percentage of poorpeople through unemployment in the district / city of Bali province. This study uses secondary data analysis PathAnalysis. The results showed showed that the negative effect of education on unemployment and wages positiveeffect on unemployment. Education and wage levels negatively affect the percentage of poor and unemployed positiveeffect on the percentage of poor people. In addition there is an indirect effect of education and wage levels on thepercentage of poor people through unemployment, in other words, unemployment is mediating variables in theinfluence of education and the level of wages on the percentage of poor people in the district / city of Bali province.